How to Think Theogically - Stone, Howard W. (Book collections on Project MUSE., 2013)
In this book, the authors contend that theology is not an optional, esoteric indulgence but rather a vital, practical skill by which people can make religious sense of concrete life situations and fulfill their intellectual vocations as Christians. Here, they have composed a theological primer for everyone. With this third edition, a lucid and lively text helps readers to probe their own theological roots and advance to a more deliberative, appreciative, and creative application of their embedded faith convictions. Addressing the how and why of theological sources, moves, and methods, the authors guide readers into major theological topics - gospel, sin and salvation, vocation, ethical discernment - through real-life case studies. The third edition has been updated and expanded with a new format focused on study aids and on highlighting main themes. -- Adapted from publisher's description.